Extremely Large Non-equilibrium Tunnel Magnetoresistance Ratio in CoRhMnGe Based Magnetic Tunnel Junction by Interface Modification - Feng, Yu; Cheng, Zhenxiang; Wang, Xiaotian (Frontiers in Chemistry, 2019)
Equiatomic quaternary Heusler compounds (EQHCs) generally have advantages of high Curie temperature, large spin polarization and long spin diffusion length, and they are regarded as one of the most promising candidates for spintronics devices. Herein, we report a theoretical investigation on an EQHC CoRhMnGe based magnetic tunnel junction (MTJ) with (i) MnGe-terminated interface and (ii) modified pure Mn terminated interface, i.e., MnMn-terminated interface. By employing first principles calculations combine with nonequilibrium Green’s function, the local density of states (LDOS), transmission coefficient, spin-polarized current, tunnel magnetoresistance (TMR) ratio and spin injection efficiency (SIE) as a function of bias voltage are studied. It reveals that when the MTJ under equilibrium state, TMR ratio of MnGe-terminated structure is as high as 3438%. When the MTJ is modified to MnMn-terminated interface, TMR ratio at equilibrium is enhanced to 2×105%, and spin filtering effect also get strengthened. When bias voltage is applied to the MTJ, the TMR ratio of the MnGe-terminated structure suffers dramatically loss. While the modified MnMn-terminated structure could preserve a large TMR value of 1×105% even bias voltage rises up to 0.1V, showing a robust bias endurance. These excellent spin transport properties make the CoRhMnGe a promising candidate material for spintronics device.